Psycholinguistic Mechanisms of Understanding Contemporary Poetry by Future Philologists - Наталія Михальчук; Ернест Івашкевич; Інна Ногачевська; Олександр Набочук; Оксана Войтенко (Психолінгвістика, 2021)
The purpose of the article is to conduct the empirical study of understanding contemporary poetry by future philologists, which helps us to distinguish psycholinguistic mechanisms of such understanding.